Choral Conducting Studies and Tools Required for the Development of Children´s Choirs. Current Situation in Costa Rica and Spain - Carlos Fernando Chaves-Cordero; Catalina Escamilla-Fonseca (Universidad Nacional, Costa Rica, 2016)
This qualitative research seeks to understand the current situation of choral conducting studies in Costa Rica and Spain, emphasizing on the tools required to work with children´s choirs. The curriculum of choral conducting careers at the Universidad Nacional de Costa Rica and the Real Conservatorio Superior de Música de Madrid was studied by means of an analysis of documents and an analytic comparison with the SWOT method. The study of plans primarily focused on subjects related to pedagogy and singing as essential foundations in the specific area of children's choirs. Additionally, an analysis of interviews to choral directors from both countries visualized the experiences of directors in their performance with children´s choirs, what skills were acquired in their undergraduate education, as well their perception of what should change or adjust in the curriculum. Significant shortcomings were perceived in teacher's training in relation with the subjects of the career. A strengthening with more contents in teaching methodologies and pedagogical resources was suggested.